Revitalisasi Manajemen BUMDes untuk Peningkatan Perekonomian Desa Kelubir, Bulungan Kalimantan Utara - Deo Ginoki, Algin; Handari Adji , Widwi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This research focuses on the revitalization of Village-Owned Enterprises (BUMDes) in Kelubir, Tanjung Palas Utara, Bulungan, North Kalimantan, which aims to improve the economic condition of the village. The research was conducted from October to December 2024, using descriptive qualitative methods to collect data through interviews, field notes and other documentation. The establishment of BUMDes MitraSejahtera Kelubir is anticipated to significantly impact the village government by increasing local revenue, developing local products, and improving Kelubir's overall economy. Despite the potential, BUMDes MitraSejahtera Kelubir faces several management challenges that require serious attention. Existing conditions reveal critical issues that hinder effective management and operational success. The study also highlights the importance of BUMDes as legal entities established by villages to manage businesses, utilize assets, and deliver public services, ultimately contributing to the welfare of village communities. The findings show that with proper management and support, BUMDes can create employment opportunities and reduce unemployment rates, thereby promoting economic growth in the village.